Collaboration of neuroscience in the care of victims of traumatic brain injury - Farias, Wanderson Santos de; Silva, Uanderson Pereira da; Silva, Anne Brandão; Arruda, Marina Costa; Farias, Luana Lima de; Soares, Andrea da Silva Barbosa; Barbosa, Gislaine Maria; Barbosa, Karina Raquel Barreto; Farias, Monique Ellen de Sousa e Silva (Seven Editora, 2023)
TEC is an injury that has been investigated mainly in terms of epidemiological aspects and care protocols. Neuroscience aims to study the nervous system, its embryonic and histological formation, as well as the connection of the physiology of the whole body, for which it has collaborated to understand the stimulus-response mechanisms, a mechanism that is important to understand the body's response. human in injuries such as TEC. Based on this principle, the problem raised for this research was: What care is offered to TEC victims and the collaboration of neuroscience. Therefore, the main objective of this study was to describe the pathophysiology of TEC, the therapeutic support for victims of this condition and the collaboration of neuroscience. This study is an integrative review. Therefore, the following guiding question was elaborated: What care is offered to patients who are victims of TEC and the collaboration of neuroscience. motor, sensory, cognitive, language, emotional or even behavioral. DOI:https://doi.org/10.56238/innovhealthknow-025